Bharthari : A Chhattisgarhi Folk Epic - Tiwari, Nandkishore; Khan, H U (tr); Macwan, Arvind (tr) (New Delhi Sahitya Akademi, 2002)
Study on folk epic Bharatharī, Raja of Ujjain, 10th cent. and folk literature of Chattisgarh, India
Keywords: Folklore : Chhattisgarh - India